The Role of Ramadhan Flash Islamic Boarding School Activities in Shaping Students' Religious Character at Pengampelan Elementary School - Dega Sopyan; Deayu Tania Putri; Aprini Rumondang Manullang; Nabila Nabila; Muhamad Arif Hidayatullah; Maulana Dinnansyah (Civiliza Publishing, Indonesia., 2026)
One of the character values ​​that needs to be instilled from an early age is religious character. Schools play a crucial role in instilling religious values ​​through various learning and extracurricular activities. One activity frequently held in schools during Ramadan is the